2018
DOI: 10.4103/atm.atm_36_18
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep in concurrent users of alcohol, khat, and tobacco smoking in community-dwelling Ethiopian adults

Abstract: BACKGROUND:Polysubstance dependence, stress, and sleep disturbances are inter-related by shared physiological pathways. No study has investigated the relationship between sleep and concurrent use of alcohol and khat.OBJECTIVES:The aim of the study was to assess the effect of the concurrent use of alcohol and khat as well as concurrent alcohol, khat, and tobacco smoking on sleep patterns.METHODS:A sample of community-dwelling adults (n = 339, age = 25.5 ± 5.7 years, body mass index = 22.0 ± 2.2 kg/m2) from Miza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…As for the present study’s result, current khat chewers have demonstrated three times higher odds of poor sleep quality than non-khat chewers. This finding aligns with studies performed in Yemen and Ethiopia ( 25 , 26 , 62 , 64 ). This could be due to the effect of khat.…”
Section: Discussionsupporting
confidence: 92%
“…As for the present study’s result, current khat chewers have demonstrated three times higher odds of poor sleep quality than non-khat chewers. This finding aligns with studies performed in Yemen and Ethiopia ( 25 , 26 , 62 , 64 ). This could be due to the effect of khat.…”
Section: Discussionsupporting
confidence: 92%
“…Although Ethiopian health care is burdened with infection-borne diseases, recent research shows an alarming increase in sleep-related disorders as well. [ 43 44 45 ] Therefore, this study's finding of adequate psychometric validation for a readily accessible and easily administrable tool to screen apnea in this population of young people from Ethiopia may be very helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another aspect in the relationship between smoking and poor sleep quality is their common effect on other unhealthy habits. In fact, many studies have shown this effect in bad nutrition, caffeine intake, alcohol consumption, illicit drug usage and lack of physical activity [55][56][57][58][59][60][61].…”
Section: Smoking and Sleep Qualitymentioning
confidence: 99%